Analyzing the optimal tilt angles of solar panels to improve the efficiency of solar energy production in Iraq - Makassees, Mohammed Dinar Sayhood; Mikhailovich, Barbin Nikolay (Journal of Ecohumanism, 2024)
Considering the aspiration to achieve sustainability in various fields, including energy, this study aims to identify the optimal angles for solar panel tilt in Iraq, specifically in three cities: Baghdad, Basra, and Mosul, with the aim of promoting the use of solar energy as a clean, renewable energy source. In light of the global energy crisis, a quantitative analytical methodology was used, utilizing historical solar radiation data spanning 18 years (2006-2024) to determine the optimal angles for receiving the best amount of solar radiation. The results showed that the optimal angles ranged between 28° in Basra, 31° in Baghdad, and 33° in Mosul. The results also indicated that various climatic influences, such as high temperatures, dust, and wind speed, affected the performance of solar panels, especially in the summer and winter. Therefore, the study recommends the use of a monthly angle adjustment system to achieve solar radiation utilization using Mono-Si solar panels, given their high efficiency under the prevailing climatic conditions.